2023
DOI: 10.1111/bcp.15817
|View full text |Cite
|
Sign up to set email alerts
|

An unusual occurrence of autoimmune pancreatitis after gam‐Covid‐Vac (Sputnik V): A case report and literature review

Abstract: The safety profile of the Sputnik V vaccine is generally reassuring. Nevertheless, an enhanced risk of new‐onset of immune‐mediated diseases has been increasingly reported following the adenoviral‐based Covid‐19 vaccine, including inflammatory arthritis, Guillain‐Barré syndrome, optical neuromyelitis, acute disseminated encephalomyelitis, subacute thyroiditis and acute liver injury as well as glomerulopathy. However, no case of autoimmune pancreatitis has been reported yet. Herein, we describe a case of type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recent reports have indicated that COVID-19 vaccinations using mRNA or viral vector vaccines can trigger autoimmune diseases such as sialadenitis, autoimmune hepatitis (AIH), or autoimmune pancreatitis (AIP) in selected individuals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In the literature, several reports have treated the correlation between autoimmune pancreatitis and COVID-19 vaccination ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have indicated that COVID-19 vaccinations using mRNA or viral vector vaccines can trigger autoimmune diseases such as sialadenitis, autoimmune hepatitis (AIH), or autoimmune pancreatitis (AIP) in selected individuals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In the literature, several reports have treated the correlation between autoimmune pancreatitis and COVID-19 vaccination ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the first hypothesis, the are many molecular similarities between the products of mRNA viral vaccine and viral proteome; thus, the mechanism leading to AIP could be the same as in viral infection. In the literature, authors postulate that AIP during COVID-19 infection may be caused by a too high affinity of viral glycoproteins to the angiotensin II receptor, highly expressed in the pancreatic tissue, consequently triggering an autoimmune process [ 59 , 66 ]. According to other hypotheses, the molecular mimicry between the viral glycoproteins and autoantigens could be a trigger for the synthesis of cross-reacting antibodies, leading to autoimmune diseases [ 59 , 67 ].…”
Section: Discussionmentioning
confidence: 99%